Drug-Related Deaths Among Young People Involved in The Criminal Justice System: A Whole-Population Multi-Sectoral Data Linkage Study - Jesse T Young; Holly Tibble; Rohan Borschmann; Stuart A Kinner (International Journal of Population Data Science, 2020)
Introduction Drug-related death is substantially higher in formerly incarcerated adults compared to the general population. Despite this, remarkably little is known about the epidemiology of drug-related death among justice-involved adolescents. A richer understanding of drug-related mortality in justice-involved young people is essential for the development of effective, evidence-based interventions for this vulnerable group.